Diaspora Missiology: A Contemporary Paradigm for the 21st Century Refugee Ministry - Kodiyattil, Praveen (Asian Horizons, 2024)
The refugee crisis is a pressing global issue, with millions of individuals forced to flee their homes due to conflict, persecution, and oppression. The church has a crucial role to play in responding to this crisis, as exemplified by Jesus’ teachings on hospitality and love for strangers. This paper explores the concept of Diaspora Missiology, which focuses on understanding and engaging in God’s redemptive mission among individuals who reside in locations other than their own homeland. It highlights the need for the church to prioritise the well-being of marginalised individuals, including refugees, and to mobilise Christians to actively participate in refugee ministry. The paper also discusses the response of the church and state to the refugee crisis, emphasising the need for a more compassionate and coordinated response that acknowledges the inherent dignity and worth of every human being. Additionally, it suggests innovative strategies to transform the challenge posed by refugees into a valuable resource, such as language training, skills enhancement, and community-sponsored resettlement programs. Overall, the paper argues that the church has a critical role to play in addressing the refugee crisis and promoting a world where love, justice, and hospitality triumph over fear, indifference, and division.